Structure and Conformation of Photosynthetic Pigments and Related Compounds. 10. Comparison of a Phytochlorin and Phytoporphyrin Derived from Chlorophyll a - SENGE, MATHIAS (International Union of Crystallography, 1997)
The crystal and molecular structures of 17-decarboxyethyl-131-deoxo-17-propylphytochlorin, C33H40N4, (1), and phytoporphyrin methyl ester, C34H36N4O3, (2), are compared. Compound (1) shows structural parameters similar to those of other naturally occurring phytochlorins. Owing to the absence of any heteroatom functionalities at the periphery, no close contacts are observed in the packing of (1), in contrast to those normally found in other chlorophyll derivatives. Compound (2) presents the first structure of a free-base pheoporphyrin and forms chains stabilized by C-H O=C and Pi - Pi interactions. In contrast to the structure of (1) and other chlorins, the two pyrrole H atoms in (2) are located at rings B and D.
PUBLISHED
Keywords: crystal and molecular structures; crystal and molecular structures